2015
DOI: 10.1016/j.neuroimage.2014.12.077
|View full text |Cite
|
Sign up to set email alerts
|

Language–motor interference reflected in MEG beta oscillations

Abstract: The involvement of the brain's motor system in action-related language processing can lead to overt interference with simultaneous action execution. The aim of the current study was to find evidence for this behavioural interference effect and to investigate its neurophysiological correlates using oscillatory MEG analysis. Subjects performed a semantic decision task on single action verbs, describing actions executed with the hands or the feet, and abstract verbs. Right hand button press responses were given f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
52
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 78 publications
7
52
0
Order By: Relevance
“…Comparison of their results highlights the advantage of MEG over EEG in capturing verb-related beta oscillations (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and their modulations that were previously reported for synchronous MEG and EEG recordings (Nikulin, Nikulina, Yamashita, Rossi, & Kähkönen, 2005). MEG studies (Klepp et al, 2015;Niccolai et al, 2014) demonstrated that action verb processing was accompanied by suppression of sensorimotor oscillations within beta frequency band (15-25 Hz), starting 250 ms after verb presentation. Whereas in EEG studies, the changes in sensorimotor oscillatory activity during action verb presentation were reported mainly for the mu/alpha frequency range (van Elk et al, 2010), with no reliable beta suppression in the EEG electrodes positioned over the motor cortex (Schaller et al, 2017).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Comparison of their results highlights the advantage of MEG over EEG in capturing verb-related beta oscillations (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and their modulations that were previously reported for synchronous MEG and EEG recordings (Nikulin, Nikulina, Yamashita, Rossi, & Kähkönen, 2005). MEG studies (Klepp et al, 2015;Niccolai et al, 2014) demonstrated that action verb processing was accompanied by suppression of sensorimotor oscillations within beta frequency band (15-25 Hz), starting 250 ms after verb presentation. Whereas in EEG studies, the changes in sensorimotor oscillatory activity during action verb presentation were reported mainly for the mu/alpha frequency range (van Elk et al, 2010), with no reliable beta suppression in the EEG electrodes positioned over the motor cortex (Schaller et al, 2017).…”
mentioning
confidence: 75%
“…Recent EEG/MEG studies of motor-language interaction in the brain employed beta ERD to characterize brain activation elicited by action verbs (Klepp, Niccolai, Buccino, Schnitzler, & Biermann-Ruben, 2015;Niccolai et al, 2014;Schaller, Weiss, & Müller, 2017;van Elk, van Schie, Zwaan, & Bekkering, 2010). Comparison of their results highlights the advantage of MEG over EEG in capturing verb-related beta oscillations (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and their modulations that were previously reported for synchronous MEG and EEG recordings (Nikulin, Nikulina, Yamashita, Rossi, & Kähkönen, 2005).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, they further discuss that later EEG components might either reflect a second comprehension step or postcomprehension processes . In studies by Pulvermüller, Härle, and Hummel (2001) and Klepp, Niccolai, Buccino, Schnitzler, and Biermann-Ruben (2015), effects concerning brain responses to action language stimuli were also reported as early as 250 ms and 400-600 ms post action verb onset. It needs to be taken into account, though, that these studies firstly presented single action verbs not embedded in a sentence context.…”
Section: Discussionmentioning
confidence: 96%
“…Secondly, Pulvermüller et al (2001) did not analyze a specific frequency range but focused on ERP differences between electrodes. Thirdly, only the study by Klepp et al (2015) used abstract verbs as a comparative condition. These methodological differences need to be considered when comparing the current results to those of earlier studies.…”
Section: Discussionmentioning
confidence: 99%